2022
DOI: 10.3389/fimmu.2022.1019404
|View full text |Cite
|
Sign up to set email alerts
|

Why vaccines fail against Piscirickettsiosis in farmed salmon and trout and how to avoid it: A review

Abstract: Piscirickettsiosis is the most severe, persistent, and damaging disease that has affected the Chilean salmon industry since its origins in the 1980s. As a preventive strategy for this disease, different vaccines have been developed and used over the last 30 years. However, vaccinated salmon and trout frequently die in the sea cages and the use of antibiotics is still high demonstrating the low efficiency of the available vaccines. The reasons why the vaccines fail so often are still debated, but it could invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…Active propagation of the vaccine strain is likely to be a prerequisite for exploiting the full potential of live attenuated vaccines. These results therefore identify an important pitfall in the use of AJ LiVac SRS and could provide an explanation for some of the recent controversy around the efficacy of this vaccine [8,9]. Surveillance programs and scientific projects that aim at optimizing the use of this and other live vaccines for poikilothermic animals must take this factor into account and preferably utilize tools that can verify that the animals have indeed been exposed to a propagating vaccine organism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Active propagation of the vaccine strain is likely to be a prerequisite for exploiting the full potential of live attenuated vaccines. These results therefore identify an important pitfall in the use of AJ LiVac SRS and could provide an explanation for some of the recent controversy around the efficacy of this vaccine [8,9]. Surveillance programs and scientific projects that aim at optimizing the use of this and other live vaccines for poikilothermic animals must take this factor into account and preferably utilize tools that can verify that the animals have indeed been exposed to a propagating vaccine organism.…”
Section: Discussionmentioning
confidence: 93%
“…Around 95% of Atlantic salmon in Chilean regions X and XI (stocked with 141 million individuals) were vaccinated with AJ LiVac SRS in 2022. A decline in Chilean antibiotic use was observed in the years after the introduction of the vaccine, but in recent years, the use of antibiotics has started to rise again [8]. This has led to some controversy regarding the efficacy of the vaccine, and Chilean researchers recently reported that they found no effect of vaccination with AJ LiVac SRS in a laboratory challenge of vaccinated fish [9].…”
Section: Introductionmentioning
confidence: 99%
“…The hyperimmune IgYs were able to increase the survival rate of shrimps from 40% (normal diet) to 75% (0.5% IgY in diet), 7 days after infection with V. Parahaemolyticus ( 418 ). A similar approach with the antigen-heteroantibody complex used as an immunogen was applied in the case of the invention related to the production of egg yolk antibodies specific to intracellular bacteria Piscirickettsia salmoni ( 419 ), the causative agent of piscirickettsiosis, a highly severe and prevalent disease in salmon ( 420 ). The immunogen composed of inactivated cells from P. salmonis and the complex of these cells and the mouse IgG against them.…”
Section: Igy Marketmentioning
confidence: 99%
“…These clearly represent a significant economic loss in a critical food industry. While fish are vaccinated, these vaccines are not as effective as they could be due to a variety of reasons [18] , [19] , [20] . Thus, it is common practice to treat potential disease with antibiotic enhanced feed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is common practice to treat potential disease with antibiotic enhanced feed. Indeed in 2021, the Chilean aquaculture industry alone used 450 tons of antibiotics [20] . Given that fish do not eat all the feed and excrete excess antibiotics, this can lead to antibiotic resistance in both fish and human pathogens.…”
Section: Introductionmentioning
confidence: 99%